Comprehensive sequence analysis of nine Usher syndrome genes in the UK National Collaborative Usher Study. Issue 1 (1st December 2011) - Le Quesne Stabej, Polona; Saihan, Zubin; Rangesh, Nell; Steele-Stallard, Heather B; Ambrose, John; Coffey, Alison; Emmerson, Jenny; Haralambous, Elene; Hughes, Yasmin; Steel, Karen P; Luxon, Linda M; Webster, Andrew R; et al.
Abstract : Background: Usher syndrome (USH) is an autosomal recessive disorder comprising retinitis pigmentosa, hearing loss and, in some cases, vestibular dysfunction. It is clinically and genetically heterogeneous with three distinctive clinical types (I–III) and nine Usher genes identified. This study is a comprehensive clinical and genetic analysis of 172 Usher patients and evaluates the contribution of digenic inheritance. Methods: The genes MYO7A, USH1C, CDH23, PCDH15, USH1G, USH2A, GPR98, WHRN, CLRN1 and the candidate gene SLC4A7 were sequenced in 172 UK Usher patients, regardless of clinical type. Results: No subject had definite mutations (nonsense, frameshift or consensus splice site mutations) in two different USH genes. Novel missense variants were classified UV1-4 (unclassified variant): UV4 is 'probably pathogenic', based on control frequency <0.23%, identification in trans to a pathogenic/probably pathogenic mutation and segregation with USH in only one family; and UV3 ('likely pathogenic') as above, but no information on phase. Overall 79% of identified pathogenic/UV4/UV3 variants were truncating and 21% were missense changes. MYO7A accounted for 53.2%, and USH1C for 14.9% of USH1 families (USH1C:c.496+1G>A being the most common USH1 mutation in the cohort). USH2A was responsible for 79.3% of USH2 families and GPR98 for only 6.6%. No mutations were found in USH1G, WHRN or SLC4A7 . Conclusions: One or two pathogenic/likely pathogenic variants were identified in 86% of cases. No convincing cases of digenic inheritance were found. It is concluded that digenic inheritance does not make a significant contribution to Usher syndrome; the observation of multiple variants in different genes is likely to reflect polymorphic variation, rather than digenic effects.